Analisis Kemampuan Menyimak Siswa Kelas V Menggunakan Media Audio Storytelling Pada Mata Pelajaran Bahasa Indonesia - Imas Siti Neneh Maesaroh; Fajar Nugraha; Hanny Latifah (Jurnal PGMI UNIGA, 2026)
This research is driven by the importance of listening skills in elementary school Indonesian language learning, where many students still face difficulties in concentrating, understanding story content, and processing auditory information. This study aims to analyze the listening abilities of fifth-grade students at SDN 2 Surabaya through the use of audio storytelling media. Using a descriptive qualitative approach, data were collected from 25 students and one teacher through tests, observations, interviews, and documentation. The results indicate that the application of audio storytelling media significantly improves students' abilities in three key areas: identifying main ideas, retelling story content coherently, and understanding implied meanings. The contextual and expressive presentation of stories proved effective in fostering students' active engagement in the learning process. In conclusion, audio storytelling serves as an effective and interactive alternative learning medium to enhance the quality of Indonesian language instruction, particularly for listening skills in elementary education. Keywords: Listening Skills, Audio Storytelling, Indonesian Language, Elementary School.